Dietary salt intake and time to relapse in paediatric multiple sclerosis. Issue 12 (24th June 2016) - Nourbakhsh, Bardia; Graves, Jennifer; Casper, T Charles; Lulu, Sabeen; Waldman, Amy; Belman, Anita; Greenberg, Benjamin; Weinstock-Guttman, Bianca; Aaen, Gregory; Tillema, Jan-Mendelt; Hart, Janace; Ness, Jayne; et al.
Abstract : Background: Salt intake was reported to be associated with increased clinical and MRI activity in adult patients with relapsing-remitting multiple sclerosis (MS). Objective: To determine if salt intake is associated with time to relapse in patients with paediatric-onset MS. Methods: Paediatric-onset MS and patients with clinically isolated syndrome (CIS) within 4 years of disease onset were recruited from 15 paediatric MS centres in the USA as part of a case–control study. Patients with available prospective relapse data subsequent to enrolment were included in this project. Dietary sodium intake was assessed by self-report questionnaire using the validated Block Kids Food Screener. Cox proportional-hazards regression models were employed to determine the association of sodium density, excess sodium intake and sodium density tertiles with time to relapse following study enrolment, adjusting for several confounders. Results: 174 relapsing-remitting MS/CIS patients were included in this analysis (mean age of 15.0 years, and 64.9% females). Median duration of follow-up was 1.8 years. In an unadjusted analysis, density of daily sodium intake was not associated with time to relapse, and patients with excess sodium intake had no decrease in time to relapse as compared with patients with non-excess sodium intake. The multivariable analysis demonstrated that patients in the medium and high tertile of sodium density had a HR of 0.69 (95% CI 0.37 to 1.30, p=0.25) and 1.37 (95% CI 0.74 to 2.51, p=0.32) compared with patients in the lowest tertile, respectively. Conclusions: Higher salt intake was not associated with decreased time to relapse in patients with paediatric-onset MS.